Constitutional Control, Protection of Fundamental Rights and Freedoms and the Sixth Amendment to the Constitution of the Republic of Bulgaria - Molloff, Stoil (Yearbook of the Law Department, 2023)
The article traces the changes in the access to constitutional justice, adopted with the Law on Amendments and Supplements to the Constitution of the Republic of Bulgaria (promulgated SG Nº106 of 22.12.2023), as well as the subsequent Decision No13 of 26 July 2024 on constitutional case Nº1/2024 of the Constitutional Court. The expansion of the application of direct and indirect constitutional control and the continued abstention of the constitutional legislator from the introduction of an individual constitutional complaint are examined.